Multicenter Investigation of the Opioid Antagonist Nalmefene in the Treatment of Pathological Gambling - Grant, Jon E.; Potenza, Marc N.; Hollander, Eric; Cunningham-Williams, Renee; Nurminen, Tommi; Smits, Gerard; Kallio, Antero (The American journal of psychiatry, 2006)
OBJECTIVE: Pathological gambling is a disabling disorder experienced by approximately 1%-2% of adults and for which there are few empirically validated treatments. The authors examined the efficacy and tolerability of the opioid antagonist nalmefene in the treatment of adults with pathological gambling. METHOD: A 16-week, randomized, dose-ranging, double-blind, placebo-controlled trial was conducted at 15 outpatient treatment centers across the United States between March 2002 and April 2003. Two hundred seven persons with DSM-IV pathological gambling were randomly assigned to receive nalmefene (25 mg day, 50 mg day, or 100 mg day) or placebo. Scores on the primary outcome measure (Yale-Brown Obsessive Compulsive Scale Modified for Pathological Gambling) were analyzed by using a linear mixed-effects model. RESULTS: Estimated regression coefficients showed that the 25 mg day and 50 mg day nalmefene groups had significantly different scores on the Yale-Brown Obsessive Compulsive Scale Modified for Pathological Gambling, compared to the placebo group. A total of 59.2% of the subjects who received 25 mg day of nalmefene were rated as "much improved" or "very much improved" at the last evaluation, compared to 34.0% of those who received placebo. Adverse experiences included nausea, dizziness, and insomnia. CONCLUSIONS: Subjects who received nalmefene had a statistically significant reduction in severity of pathological gambling. Low-dose nalmefene (25 mg day) appeared efficacious and was associated with few adverse events. Higher doses (50 mg day and 100 mg day) resulted in intolerable side effects.